Surfactant inhibits ATP-induced release of interleukin-1β via nicotinic acetylcholine receptors - Backhaus, Sören (J Lipid Res, 2017)
Interleukin (IL)-1β is a potent pro-inflammatory cytokine of innate immunity involved in host defense. High systemic IL-1β levels, however, cause life-threatening inflammatory diseases, including systemic inflammatory response syndrome. In response to various danger signals, the pro-form of IL-1β is synthesized and stays in the cytoplasm unless a second signal, such as extracellular ATP, activates the inflammasome, which enables processing and release of mature IL-1β. As pulmonary surfactant is known for its anti-inflammatory properties, we hypothesize that surfactant inhibits ATP-induced release of IL-1β. Lipopolysaccharide-primed monocytic U937 cells were stimulated with an ATP analog in the presence of natural or synthetic surfactant composed of recombinant surfactant protein (rSP)-C, palmitoylphosphatidylglycerol, and dipalmitoylphosphatidylcholine (DPPC). Both surfactant preparations dose-dependently inhibited IL-1β release from U937 cells. DPPC was the active constituent of surfactant, whereas rSP-C and palmitoylphosphatidylglycerol were inactive. DPPC was also effective in primary mononuclear leukocytes isolated from human blood. Experiments with nicotinic antagonists, siRNA technology, and patch-clamp experiments suggested that stimulation of nicotinic acetylcholine receptors (nAChRs) containing subunit α9 results in a complete inhibition of the ion channel function of ATP receptor, P2X7. In conclusion, the surfactant constituent, DPPC, efficiently inhibits ATP-induced inflammasome activation and maturation of IL-1β in human monocytes by a mechanism involving nAChRs.